Evaluation of site-specific management to optimise Vitis vinifera L. (cv. Tannat) production in a vineyard with high heterogeneity - Gustavo Pereyra; Anne Pellegrino; Remi Gaudin; Milka Ferrer (OENO One, 2022)
The spatial variability of vineyards can be characterised through precision viticulture that will allow setting the boundaries of homogeneous management zones. This study aimed to evaluate the impact of soil and plant management (site-specific management) to increase yields and improve berry quality. During three consecutive seasons, contrasting treatments designed ad hoc for two zones of vigour pre-established by NDVI were tested: high vigour zone (HV) and low vigour zone (LV). The treatments were aimed at reducing water and nitrogen supply and improving microclimatic conditions in the cluster zone in the HV zone. In the LV zone, treatments were aimed at increasing water and nitrogen supply. Leaf removal in the HV zone was the most efficient treatment to improve productivity and quality. Moreover, the water restriction improved grape quality, especially in a rainy year. The regulated deficit irrigation strategy applied in the LV zone at specific phenological stages was shown to increase vegetative growth, yield and to improve grape anthocyanins and phenols contents. The benefits of additional nitrogen supply in the LV zone on plant nitrogen status, yield, and berry composition were highly dependent on water availability. Ultimately, this study provided new insights into the relationship between water and nitrogen availability and how this determines vigour and influences yield and grape quality and influences the deviation from a “Productive Target” pattern. The use of site-specific techniques could be adjusted on a small production scale, thanks to mapping carried out with precision viticulture technologies.